Study on Bond Anchorage Behavior of Small-Diameter Rebar Planting under Medium and Low Cycle Fatigue Loads - Kui Chen; Linhao Zhang; Xianqiao Wang (Applied Sciences, 2023)
In this paper, we describe how, through the combination of field testing and finite element simulation, the bonding and anchoring performance of small-diameter rebar under the action of medium and low cycle fatigue load was studied and the corresponding conclusions were obtained: ① Through the test, the performance parameters of the 6 mm and 8 mm rebar planting specimens were obtained after the rebar was subjected to 10,000, 50,000 and 100,000 times of medium and low cycle fatigue loading at depths of 10d, 15d and 20d. The analysis shows that the medium and low cycle fatigue load has a significant effect on the elastic ultimate load, elastic ultimate slip and ultimate slip of the small-diameter rebar planting specimens. With the increase in fatigue loading times, the elastic ultimate load of the rebar specimen decreased continuously, and the elastic ultimate slip and ultimate slip showed an increasing trend. By increasing the anchor depth, the influence of fatigue load on the anchoring performance parameters of the rebar planting specimen can be reduced. Under the influence of the upper ultimate condition of 100,000 times of fatigue loading, the ultimate load and failure mode of the planted bars basically did not change compared with the control specimens without fatigue loading. ② Based on the performance parameters of the rebar planting specimens obtained from the field test, the bond–slip constitutive relationship of the adhesive–rebar interface of the small-diameter rebar planting under the medium and low cycle fatigue load is analyzed and proposed. The F-U relationship of the spring element under the fatigue load is defined to simulate the bond–slip behavior of the adhesive–rebar interface. The finite element simulation results are in good agreement with the field test results. ③ Through a large number of finite element numerical simulation results, the elastic ultimate load calculation formulas of 6 mm and 8 mm diameter rebar planting specimens under medium and low cycle fatigue loads are obtained.